2021
DOI: 10.3390/microorganisms9122558
|View full text |Cite
|
Sign up to set email alerts
|

Desulfovibrio desulfuricans AY5 Isolated from a Patient with Autism Spectrum Disorder Binds Iron in Low-Soluble Greigite and Pyrite

Abstract: The sulphate-reducing bacteria (SRB) of genus Desulfovibrio are a group of prokaryotes associated with autism spectrum disorders (ASD). The connection between the elevated numbers of Desulfovibrio in the gut of children with ASD compared with healthy children remains unresolved. A conceivable consequence of SRB overgrowth in the gut is the conversion of bioavailable iron into low-soluble crystalline iron sulphides, causing iron deficiency in the organism. In this study, we report the draft genome sequence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Our findings corroborate previous studies 102 indicating that vivianite is commonly produced through bacterial sulfate reduction. The biochemical processes in the SRB lifecycle lead to the formation of H 2 S, 24,42 a strong reducing agent, hence vivianite formation is predominantly observed in the presence of SRB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings corroborate previous studies 102 indicating that vivianite is commonly produced through bacterial sulfate reduction. The biochemical processes in the SRB lifecycle lead to the formation of H 2 S, 24,42 a strong reducing agent, hence vivianite formation is predominantly observed in the presence of SRB.…”
Section: Discussionmentioning
confidence: 99%
“…35 Mackinawite and greigite are the most frequently reported biomineralized phases of SRB cultures. [36][37][38][39][40][41][42][43] Recent studies have suggested that merging anaerobic digestion of waste activated sludge with in situ sulfate reduction by SRB could be a novel method for phosphate release. 8,44 However, phosphoruscontaining minerals in SRB species have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…S2), however it is important to note that the lumen of the intestine is a complex nutrient-rich environment that contains many other exogenous L-cysteine sources. It is also important to consider that streptomycin treatment was used to reduce colonization resistance in the gut, but that the resulting dysbiosis could negatively impact populations of SRBs in the gut and alter the H 2 S/thiosulfate landscape in the intestinal lumen in our experimental model, though little is known about the impacts of antibiotics on SRBs (45). Despite these observations, it is possible that the CysE/CysK pathway still contributes overall L-cysteine levels during infection, and high levels of these inorganic sulfur compounds in the intestine may represent an early host signal that primes Lm for intracellular PrfA activation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested a few mechanisms by which DSV may be responsible for ASD. One such study by Karnachuk et al identified low iron bioavailability caused by DSV as a result of its H 2 S production [ 81 ]. By binding iron, hydrogen sulfide forms iron sulfide, resulting in iron deficiency, a feature of ASD [ 82 , 83 ].…”
Section: Dsv and Diseasesmentioning
confidence: 99%